Health behaviours and their facilitation under depletion conditions: The case of snacking - Sellahewa, D.; Mullan, Barbara (2015)
Introduction: Previous research suggests that depletion (the state ensuing from self-control exertion) engenders lapses in health behaviours. The present study tested for that effect in relation to the health behaviour of limiting snacking, and investigated whether health goal-priming might facilitate such health behaviours even under depletion conditions. Method: A laboratory study was conducted involving an analytic sample of 85 undergraduates (mean age = 20.08, SD = 3.96; female: n = 63). Depletion was manipulated by having participants watch a humorous video while suppressing their responses (depletion condition) or remaining natural (non-depletion condition). The activation of participants' health goals was then manipulated by subtly exposing (goal-priming condition) or not exposing (non-priming condition) participants to health-related words in a Scrambled Sentence Task. Finally, snacking was measured using a bogus taste-test. Results and discussion: Controlling for initial hunger, snacking was higher among depleted compared to non-depleted participants. Snacking was lower among primed compared to non-primed participants. The interaction between depletion and goal-priming was not significant. These findings suggest that depletion should be recognised as a risk factor for lapses in health behaviours, and that health goal-priming may be a useful technique for facilitating such behaviours even when individuals are depleted.